HEALTH PERSONNEL AND THE REFORM OF PRIMARY HEALTH CARE IN MONTENEGRO - Scepanovic, Lidija (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Universal health coverage reform activities in primary health care in Montenegro were conducted in the period between 2004 and 2012, with the aim of increasing the efficiency of the health care system by ensuring rational use and availability of resources. The purpose of this study is to describe the health personnel during and after the reform activities in Montenegro. Materials and methods: We adapted the four-dimensional World Health Organization framework to examine availability, accessibility, acceptability and quality of the health personnel in public primary health care facilities, in Montenegro, during and after the reform. Availability, accessibility, acceptability and quality of health personnel were examined using a defined set of proxies. In addition, the latest available data on density rates of health personnel were presented, in order to examine the sustainability of the implemented reforms. The data used included primary health care information system data, data published by the Institute of Public Health of Montenegro, as well as data from a number of official and expert reports by relevant experts and institutions.Results: The total number of physicians employed in primary health care was reduced during the reform by 5%, while the number of nurses was decreased by 35%. At the same time, the number of GPs (chosen doctors for adults) increased, which improved their availability (54.4 in 2015 vs. 36.3 in 2004, per 100,000). Accessibility showed great variations among municipalities. The utilization of health care services, at the national level, increased by 25% in adult health care services. The reduction of the number of nurses was tailored to meet set norms in health care services for adults, women, and children. Reform activities improved the professional competencies of primary health care teams.Conclusion: Primary health care reform improved the availability and accessibility of health personnel and implemented activities that improved their acceptability and quality. It is recommended to establish a permanent body which would continuously monitor the functioning of the primary health care (PHC) system, as well as the changes that occur in PHC, thus ensuring that reform results are maintained and further improved.
Keywords: primary health care; health personnel; universal health coverage